Analysis of the Ability to Understand Mathematical Concepts in Terms of Curiosity Using the Geoboard Assisted Numbered Head Together (NHT) Learning Model - Reza Frastica Dewi; Zulmi Roestika Rini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study aims analyze the learning quality of the numbered head together (NHT) model in improving students' ability to understand mathematical consepts and to describe students' ability to understand mathematical consepts in terms of curiosity in learning matehmatical with the numbered head together (NHT) model. This type of research uses a combination method (mix method) with a concurrent embedded combination type. The population in this study were all study of SD N Blotongan 02, the sample in this study was grade IV of SD N Blotongan 02. The results showed that the quality of learning using the numbered head together (NHT) model was in a good category as indicated by: (1) at the planninh stage, the learning tools that have been prepared are valid, (2) at the implemntation stage, the implementation of learning is categorized as good and gets a positive response from students, and (3) at the ravluation stage, it has fulfilled the test of effectivieness influence, and increased ability to understand mathematical concepts. In addition, students with every high and high curiosity have been able to achieve the seven indicators of ability to understand mathematical concepts, while students with moderate and low curiosity have not been able to achieve the seven indicators of ability to understand mathematical concepts